Investigating electrolyte-reagent-mineral interactions in response to water quality challenges in the flotation of a PGM ore - Manono, Malibongwe Shadrach (Department of Chemical Engineering, 2019)
Froth flotation is a physicochemical process that enables the separation of valuable minerals and unwanted gangue minerals contained in an ore. It utilises the differences in surface properties of the minerals to be separated. Among other factors affecting flotation, water is a major factor as it acts as a reagent and transport medium. Therefore, it stands to reason that the quality of the water used in the process matters. Current environmental restrictions on water usage which are aimed at addressing the global scarcity of water require that mining operations recycle and reuse water within their operations. This necessitates proactive management strategies and initiatives aimed at understanding the impact that water could have on flotation and other water intensive processes. The development of such initiatives relies on the provision of sound and fundamental scientific evidence examining and decoupling the effects of water quality on the sub-processes of flotation. This would enable the creation of alternative operating conditions at which flotation could still occur without significant effects on production and profitability. Recycling of process water has for many years been the mining industry’s solution to reducing reliance on municipal water because mining operations are often located in arid regions. It has become clear that the recirculation of water in flotation circuits results in the accumulation of dissolved solids, electrolytes, unspent reagents and biological matter possibly resulting in poor flotation performance or alternatively high costs associated with water treatment. Given that water is both a reagent and transport medium in flotation, changes in its quality can significantly affect flotation performance through electrolyte-reagent-mineral interactions. This study has investigated whether there are any dominant or synergistic electrolyte-reagent interactions occurring during flotation which may impact negatively on the flotation performance. Interactions occurring in both the pulp phase and the froth phase were investigated through established bench scale flotation techniques. On the basis of available literature, investigations were carried out to identify inorganic electrolytes which had the biggest impact on froth stability as well as those which had a dominant role on depression, and specifically CMC efficacy on gangue management. A Merensky ore, typical of the South African Bushveld Igneous Complex was selected as previous work within the Centre for Minerals Research was conducted on ores of similar mineralogy. Threephase bench scale flotation and froth column tests were performed to examine the effect of increasing ionic strength of plant water and CMC dosage on froth stability and gangue recovery. Two-phase batch flotation and froth column tests were performed at various electrolytic conditions to assess the effect of ionic strength, electrolyte type and pH on froth stability using water recovery, foam height and foam collapse time as key performance indicators of froth stability. Settling tests, adsorption studies, zeta potential measurements as well as inorganic electrolyte speciation determination were considered in order to elucidate the role of water quality on gangue depression. Talc and pyrrhotite were selected as proxies for naturally floatable gangue (NFG) and sulphides respectively in order to simulate the possible behaviour of a Merensky ore. Increasing the ionic strength resulted in increased solids and water recoveries suggesting an enhancement in froth stability. When the effect of ionic strength on CMC behaviour was investigated under changing pH, results showed that contrary to findings at pH 9 which showed increases in solids recovery with increasing ionic strength, solids recovered decreased with increasing ionic strength at pH 11. This suggested that at higher pH levels above pH 10 there are hydroxy species present which inhibit the floatability of mineral particles either by forming layers on the mineral particles which hinder the action of the collector or through depressant efficacy enhancement. The speciation diagrams indicated that beyond pH 10, species such as CaOH+ increased in concentration especially at the higher ionic strength. Furthermore the zeta potential results for talc and pyrrhotite showed that at pH 11, the potentials were less negative compared to pH 9 for all synthetic plant waters proving that at pH 11 the pulp chemistry would exhibit a more depressive nature onto mineral particles owing to increased concentrations of positively charged hydroxo species at pH 11 compared to pH 9. These hydroxy species such as CaOH+ would adsorb onto the negatively charged mineral particle, reducing the negative surface charge of the mineral particle. Water recoveries increased with increasing ionic strength at both pH 9 and pH 11. These findings were further supported by 2-phase froth column tests in which water recoveries, foam height, and foam collapse time increased with increasing ionic strengths. This increase in froth stability with increasing ionic strength at both pH conditions is attributed to an increase in the [Ca2+], [Mg2+] and [SO4 2- ] which reduces bubble coalescence. Upon the determination of NFG recovery, entrained gangue recovery and total gangue recovery, it became clear that, at increasing ionic strength, there was a decrease in the recovery of NFG and entrained gangue per g of water recovered. The decrease in the recovery of NFG and entrained gangue per unit water was attributed to the coagulative nature of gangue in the presence of highly concentrated electrolytes and CMC. The fact that total NFG recovery did not change with water quality at a fixed CMC dosage but decreased with increasing ionic CMC dosage is indicative of the strong susceptibility of NFG depression to CMC dosage to an extent that at hyper dosages such as 500 g/t, all NFG is depressed completely. However, given the relationship between solids entrained and water recovery, the total recovery of entrained gangue increased with increasing ionic strength due to increased volumes of water which reported to the concentrate at increasing ionic strength. It was also shown that there was no change in sulphide recovery with increasing ionic strength. This was indicative of preferential adsorption of CMC onto gangue at the conditions tested. Higher solids recoveries or mass pulls were largely due to increased gangue recovery, mainly entrained gangue, which increased with increasing ionic strength. It was thus postulated that at increased ionic strengths, CMC coagulated gangue particles whilst indirectly destabilising the froth and retarding the action of electrolytes on froth stability through the removal of froth stabilising NFG. In order to examine coagulation at increasing ionic strengths, settling tests were performed on a Merensky ore and on pure talc. The results showed reduced settling time with increasing ionic strength and increasing CMC dosage suggesting that in a flotation cell, highly concentrated electrolytes would assist in depression by enhancing the coagulation of gangue and thereby decreasing their floatability. This can be attributed to increased concentrations of Ca2+ and CaOH+ which adsorb onto gangue; adsorption of which is the mechanism through which the chemisorption of CMC onto gangue occurs. In considering the effect of ionic strength and CMC dosage on froth stability, three phase froth column test results showed that the froth collapse time and froth height increased with increasing ionic strength due to an increase in the concentration of inorganic electrolytes which inhibit the coalescence of bubbles. In fact, Ca2+, Cl- , Mg2+, Na+, NO3 - and SO4 2- , which are present in the tested synthetic plant waters, are all reported in literature to have the ability to retard bubble coalescence, thus additive interactive effects in the tested systems should have been present. It was further shown that the addition of CMC resulted in a froth destabilization. The coagulation findings suggested that the presence of inorganic electrolytes enhanced the adsorption of CMC onto gangue due to changes on the mineral surface charge imposed by inorganic electrolytes. Microflotation results in the presence of CMC showed a decrease in the recovery of talc with increasing ionic strength whilst the presence of CMC did not affect the flotation behaviour of pyrrhotite. The adsorption results agreed with the microflotation results and the coagulation findings in that there was less residual CMC, meaning that more CMC was adsorbed onto the mineral surface with increasing ionic strength of plant water. In line with these findings, it was shown that the zeta potential of minerals, both talc and pyrrhotite, although investigated separately, increased (i.e. became less negative) with increasing ionic strengths. Thus, this work showed that increasing the ionic strength of plant water increased the concentration of inorganic electrolytes present in process water which acted on the mineral surface, passivating the mineral surface as seen through the less negative zeta potential in high ionic strengths. This would in turn create an environment conducive for an acid-base interaction between the hydroxyl species coated mineral particles (base) and highly negatively charged CMC ligand (acid), enhancing the preferential adsorption of CMC onto gangue as shown by the increase in the absorbed CMC concentration onto talc. The increased CMC adsorption would consequently assist in the formation of CMC-gangue mineral flocs with an induced coagulative and hydrophilic nature as shown by the shorter settling time in increasing ionic strength. Further investigations were carried out with single salts of cations and anions common in process water in order to identify whether there were any ions with the greatest froth stabilising action and gangue depression; Although Sulphide recoveries did not change with specific ions, the sulphide grades were affected by ion type owing to changes in gangue recoveries. Sulphide grades were higher with divalent ions compared to monovalent ions. It was also shown that salts containing NO3 - resulted in the lowest froth stability, as indicated by water recoveries and froth collapse time, compared to those which contained SO4 2- and Clin solution. Ca2+ and SO4 2- resulted in the highest froth stability compared to Na+. This can be attributed to a better inhibition of bubble coalescence in divalent ions compared to monovalent ions. The divalent Ca2+ and Mg2+ resulted in the lowest gangue recoveries compared to the monovalent Na+.NO3 - resulted in the least gangue recoveries compared to SO4 2- and Cl- . These findings suggested an enhanced hydrophilic nature onto gangue by divalent cations than monovalent cations with an even greater impact in NO3 - containing solutions- . Similarly, coagulation measurements showed an enhanced coagulation in NO3 - compared to SO4 2- with greater coagulation achieved in Ca2+ compared to Na+. An increase in the order of Ca(NO3)2>CaSO4>NaNO3>Na2SO4 in the zeta potential of talc and pyrrhotite was seen. This supported the enhanced coagulation and depression in Ca2+ and NO3 - containing systems. Thus, the findings of this work offer an opportunity to better understand water quality effects on flotation and their implications on froth stability and gangue management. Also, it has been shown that specific ion effects on froth stability and gangue management exist. Overall this study has shown that bench scale flotation techniques such as batch flotation, froth column flotation and microflotation can be used to understand the effect that water quality can have on a specific ore or mineral and that such techniques can be complemented with established surface chemistry laboratory techniques such as adsorption, coagulation and zeta potential to understand the interactions occurring in the air-water, air-solids and solids-water interfaces responsible for a particular flotation performance.. Through lower gangue recoveries, improved coagulation, increased adsorption and zeta potential, it can be concluded that the divalent Ca2+ is most likely to improve gangue depression and even more so in the presence of CMC compared to monovalent Na+. Moreover due to its causing a reduction of bubble coalescence, Ca2+ could result in improved froth stabilities and less entrainment. The monovalent Na+ showed higher gangue recoveries but lower water recoveries due to its weaker froth stabilising action compared to the divalent Ca2+. The higher gangue recoveries could be attributed to entrainment, meaning that given the lower froth stabilising action, Na+ richer solutions are most likely to lead to higher entrainment of gangue. Through higher water recoveries and higher froth collapse time results, it has been shown that SO4 2- ions result in better froth stabilities compared to Cl- and NO3 - ions, and would thus need to be monitored carefully for the desired froth stability. Thus, this work demonstrated the role of inorganic electrolytes on CMC efficacy and gangue depression using adsorption, coagulation and zeta potential results. These results correlated well with this study’s batch flotation and microflotation results. Also, these showed evidence to the suggestions and deductions drawn out of the bench scale flotation results on the effects and mechanisms through which inorganic electrolytes affect gangue and froth stability. This study also demonstrated that the divalent Ca2+ had the greatest froth stabilising effect and the greatest depressive effect on gangue compared to the monovalent Na+. Moreover, it provided evidence suggesting that solutions containing NO3 - were depressive on gangue and less froth stabilising compared to SO4 2- and Cl- . Findings of this work showed experimental evidence of the nature of CMC-electrolyte interaction in the pulp phase and its implications on the froth phase and gangue depression. It is believed that findings of this work offer an opportunity for flotation operations to tailor or control their water quality towards a desired flotation outcome. It may be possible that in order to combat changes in water quality, should closed water cycles be implemented, an operation could adjust their reagent suite to obtain a manageable grade and recovery and alleviate the high cost associated with cleaning of on-site water.